Effects of the scalar parameters in the Suzen-Huang model on plasma actuator characteristics - Ibrahim, Imran Halimi (2014)
Purpose – For the past decade, plasma actuators have been identified as a subset in the realm of active flow control devices. As research into plasma actuators continues to mature, computational modelling is needed to complement the investigation of the actuators. This paper seeks to address these issues.